PHARMACOLOGICAL SIGNIFICANCE OF FERULA COMMUNIS L - Sharipova Riboba Gulomalievna (Scholars Digest Publishing, 2023)
Traditional medical books such as Dioscorides report numerous beneficial uses for this plant. They are both widely used in traditional medicine to treat a wide range of ailments. A large number of chemical compounds have been isolated from this plant, including sesquiterpene coumarins and polysulfides. Fresh plant materials, crude extracts and isolated components of F. persica have demonstrated a wide range of pharmacological properties, including anti-pigment properties of Serratia marcescens., cytotoxic, antibacterial, antifungal, antileishmanial, chemoprophylactic against cancer, elimination of multidrug resistance, anti-inflammatory and inhibitory effects on lipoxygenase.
Keywords: Ferula communis L., biologically active additives, ferutin, sesquiterpene coumarins.